Standard specification for copper-nickel-zinc (nickel silver) wire and copper-nickel alloy wire
This specification establishes the requirements for wire in round, hexagonal, octagonal, rectangular, and square form of UNS Alloy Nos. C71000, C74500, C75200, C75700, C76400, C77000, and C79200. This specification is general in that the product is used in many applications where the requirements are too particular to be specified by standard test results.